Coolie Types, Trinidad - (:unkn) unknown (Stephens and Scott, Trinidad, 2008)
Photograph of two East Indian women in traditional wear. Includes a Trinidad penny stamp dated January 13th 1903.
Colour: Black, brown and white; Style: Portrait; Other: Bordered, Undivided
Keywords: Postcards; Trinidad and Tobago; Women, East Indian--Trinidad and Tobago; Ethnic costume--India; 1903; Clothing and dress--Trinidad and Tobago